Relationship between serum ferritin and endocrinopathies in thalassemic children: A hospital-based study - Kataki, Rita Panyang; Bharati, Sagarika (Indian Journal of Child Health, 2019)
Background: Thalassemia syndromes are a heterogeneous group of Mendelian disorders characterized by lack of/decreased synthesis of either ?/? globin chains of hemoglobin. It results in ineffective erythropoiesis and lysis of mature red blood cells in the spleen. Thalassemic patients require multiple blood transfusions which led to iron overload. Objective: This study evaluated endocrinopathies in thalassemic patients of age 5–18 years and relationship with serum ferritin level. Materials and Methods: This is a hospital-based cross-sectional study on 70 transfusion dependent thalassemic children of 5–18 years attending the department of pediatrics, of a tertiary care hospital in Assam. Their height, sexual maturity rating, serum ferritin, calcium, alkaline phosphatase, phosphate, thyroid stimulating hormone, random blood sugar, and fasting blood sugar were recorded. The data were analyzed statistically and p <0.05 was considered to be statistically significant. Results: The study population (70) consisted of 40 males and 30 females. In this study, 91.67% (22 of 24 cases) had delayed puberty, 50% (35 of 70) were stunted, 37.14% (26 of 70 cases) were hypocalcemic, 31.43% (22 of 70) had hypothyroidism, and 2.85% (2 of 70) were diabetic. The mean serum ferritin level was 2845±859.40 ng/ml in delayed puberty while it was 2027.50±21.92 ng/ml (p>0.05) in thalassemic children with normal puberty. The mean serum ferritin in stunted thalassemic children was 2909.86±820.93 ng/ml and it was 1421.43±283.41 ng/ml (p<0.001) in normal height thalassemics. The mean serum ferritin in hypothyroid thalassemics is 2806.59±929.57ng/ml and is 1885.75±846.89 ng/ml (p<0.001) in euthyroid cases. The mean serum ferritin in diabetic thalassemics was 2772.50±1092.48 ng/ml and it was 2147.16±965.63 ng/ml (p>0.05) in nondiabetic thalassemics. Conclusion: Growth retardation and endocrinal complications significantly occur in transfusion-dependent thalassemic children. Adequate chelation therapy helps in controlling serum ferritin levels thereby enabling chronically transfused thalassemic children to grow normally without early endocrinal complications.